Peran Musyawarah Guru Bimbingan Konseling dan Kompetensi Profesional Konselor SMP Kota Semarang - Basuki, Tentrem (Universitas Negeri Semarang, 2017)
This research aims to find out the extent of the role of MGBK in support of the profession of guidance and counselling and profesional competence of counselor MGBK member’s. The type of in this research is a survey research. Population in this research is the entire BK teacher/counselors who are members of MGBK SMP Negeri Semarang who attended the activities of MGBK, while sampling used in this research is purposive sampling technique. Data collection method using question form is the role of MGBK and profesional competence, while testing the validity of the instrument using the formula product moment and reliability of instruments with the formula Alpha, data analysis techniques used descriptive analysis of percentage. Based on the analysis results obtained average percentage of the role MGBK SMP Negeri Semarang of 64% so entered in the criteria of